Factors associated with intention to have caesarean delivery in pregnant women in China: a cross-sectional analysis. (October 2016) - Wang, Lianlian; Xu, Xianglong; Baker, Philip; Tong, Chao; Zhang, Lei; Qi, Hongbo; Zhao, Yong
Abstract: Background: The proportion of caesarean deliveries significantly increased from 2·0% in 1978––1985 to 36·6% in 2006–2010 among Chinese pregnant women. The rate reached 55% in 2014. In this study we explored the basic demographic characteristics and preferred method of delivery of pregnant women and analysed the associated social and psychological factors. Method: We did a cross-sectional analysis among pregnant women during June to August, 2015, in 16 hospitals from five provinces of mainland China. Data were collected by interview survey. Intended method of delivery was categorised as "vaginal delivery", "unsure before delivery", or "caesarean delivery". The study protocol was approved by the Ethics Committee of Chongqing Medical University (record number 2015008). All participants gave written informed consent. Findings: 1755 (75%) women in their first pregnancy and 590 (25%) in their second pregnancy were enrolled in this study. Of these, 354 (156 in first pregnancy and 198 in second pregnancy) intended to undergo caesarean delivery, 585 (25%) participants were unsure prior to delivery, and 1406 (60·0%) intended to have vaginal delivery. Ordinal logistic regression analysis found that women from ethnic minorities (n=8, 8·6%) were less likely to intend to have caesarean delivery than women from the Han Chinese population (n=346, 15·4%; β −0·4863, 95% CI −0·9588 to −0·0398), and women in mid-pregnancy (n=97, 13·8%) were less likely to intend to have caesarean delivery than women in early pregnancy (n=42, 14·3%; −0·2726, −0·5215 to −0·0209). Women in their second pregnancy (n=198, 33·6%) were more likely to intend to have caesarean delivery than those in their first pregnancy (n=156, 8·9%; 0·8526, 0·4593 to 1·0308), and those with advanced maternal age (aged ≥34 years, n=91, 37·5%) were more likely to intend to have caesarean delivery than younger mothers (263, 13·5%; 0·7454, 0·6467 to 1·0584). Interpretation: Intervention programmes should focus on women from the Han population, older pregnant women, women in the middle stages of pregnancy, and women in their first pregnancy to reduce the rate of unnecessary caesarean delivery. These findings have implications for the implementation of China's new national two-child policy. Funding: This project was supported by theMedjaden Academy and Research Foundation for Young Scientists (grant MJR20150047 ). This study was also funded by the Summer Social Practice Project of the School of Public Health and Management, Chongqing Medical University.